Synthesis, characterization and 11C‐radiolabeling of aminophenyl benzothiazoles: structural effects on the alkylation of amino group. (3rd July 2014) - Venkatachalam, T. K.; Stimson, D. H. R.; Bhalla, R.; Pierens, G. K.; Reutens, D. C.
<x xml:space="preserve">Abstract</x> Several aminophenyl benzothiazoles were prepared with a view to using them as amyloid binding agents for imaging β‐amyloid in Alzheimer's disease. These precursors were radiolabeled with 11C‐positron‐emitting radioisotope using an automated synthesizer and selected radiolabeled compounds were further purified by HPLC. Our results demonstrate that changes in structure have a major influence on the radioactive yield and the ease with which the radiolabel can be introduced. Aminophenyl benzothiazoles with an attached isopropyl group resisted dialkylation perhaps due to steric hindrance caused by this group. Straight chain attachment of methyl, ethyl, butyl, and crotyl groups in the structure decreased the radiochemical yield. Notably, the o‐aminophenyl benzothiazole derivatives were difficult to alkylate despite stringent experimental conditions. This reactivity difference is attributed to the hydrogen bonding characteristics of the o‐amino group with the nitrogen atom of the thiazole ring.